Mastery of Indonesian Vocabulary through Crossword Puzzle Media for Students of SD 04 Pasir Angin - Vickry Ramdhan; Ramliyana, Randi (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2024)
Students' use of vocabulary is crucial for expressing ideas and thoughts. However, a number of studies demonstrate that language proficiency is still lacking among elementary school pupils. Creating educational media is one endeavour that can be undertaken. The purpose of this study is to provide crossword puzzle learning resources for Indonesian language instruction in order to enhance class III students vocabulary knowledge at SDN Pasir Angin 4. The present study employed a qualitative research methodology. 30 class III students, 15 of whom were female and 15 of whom were male, served as the research subjects for this study at SDN Pasir Angin 4 Elementary School. Using methods of observation and documentation, research data was gathered. The crossword puzzle learning medium that has been designed is worth a try, according to the assessment data that was collected. The kids in SDN Pasir Angin 4 class responded well to the Indonesian language learning play material in my classroom using the question-and-answer format with crossword puzzle learning media.